Host Diversity of Beauveria bassiana (Balsamo) Vuillemin in Rice Field in Bolaang Mongondow Regency - Siahaan, Parluhutan; Saroyo, Saroyo; Langoy, Marnix L.D.; Saimima, Arie J. (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2021)
Beauveria bassiana can attack a variety of hosts and their virulence can vary at each host and location. Exploration of the diversity of hosts B. bassiana from local isolates needs to be done as initial information that can explain the ability of B. bassiana in infecting insects. Sampling locations were selected in three district, each district selected three stations and each station consisted of 10 plots. The location of sampling is determined by the purposive random sampling method. Each station was made a plot measuring 1m x 1m and distributed randomly. Every insect infected with B. bassiana was taken and taken to a laboratory for identification. The results showed that there were five insects that hosted B. bassiana, namely Nilaparvata lugens, Scotinophara coarctata, Leptocorisa oratorius, Nezara viridula and Paraeucosmetus pallicornis. The highest host diversity index was found in North Dumoga with a value of 1.47. The highest abundance index was found in N. lugens host in East Dumoga with a value of 43%. The highest density was found in the host N. lugens in Central Dumoga with a value of 1.93 ind / m2. There were indications of differences in virulence of the B. bassiana local isolates that were influenced by the spesies of host and location Keywords: Beauveria bassiana, diversity, Bolaang Mogondow Regency, diversity and abundance indices